Pengaruh Promosi dan Citra Merek terhadap Keputusan Pembelian Fashion di TikTok Shop - Paryanti, Dwi; Febrian, Habil; Rahadhini, Marjam Desma (Amsir Management Journal, 2025)
This study examines the influence of promotion and brand image on the decision to purchase fashion products on the TikTok Shop e-commerce platform by Generation Z in Surakarta. The method used was quantitative with the distribution of questionnaires and regression analysis to test the relationships between variables. The results show that promotion and brand image have a significant effect on consumers' purchasing decisions. These findings underscore the importance of effective digital marketing strategies on social media platforms. The implications of this research provide insight for business actors in optimizing promotions and building brand image to increase purchases on TikTok Shop.